Pengalaman dan Pemaknaan Mahasiswa Psikologi dalam Menggunakan Jasa Tarot - Unique Lecyana Arraudah; Zain Darin Zalfaa; Dwi Hardani Oktawirawan (Yayasan Literasi Sains Indonesia, 2026)
The contemporary utilization of tarot extends beyond its traditional role in fortune-telling, serving also as a tool for self-reflection and the pursuit of personal meaning. This phenomenon is particularly intriguing when observed among psychology students, who are academically trained in scientific methodologies and empirical reasoning. This study seeks to explore the subjective experiences of psychology students who engage with tarot reading services and to understand how they reconcile this practice with their science-based academic training. Employing a qualitative research design, the study utilizes the interpretative phenomenological analysis (IPA) method. The participants comprised three psychology students who had previously engaged with tarot reading services. Data were gathered through semi-structured interviews and analyzed following IPA procedures. The findings indicate that tarot is employed in contexts involving romantic issues and personal dilemmas, functioning as a means to reinforce evaluations, guide decision-making, facilitate self-reflection, and provide validation and emotional reassurance. Despite being epistemologically distinct from psychology, participants perceive tarot and psychology as two separate domains that can coexist within personal experience. These findings underscore the capacity of individuals to navigate multiple frameworks of meaning simultaneously, thereby maintaining coherence between experience and belief in daily life. The implications suggest that, within the context of contemporary life, psychology students are adept at negotiating scientific knowledge alongside practices of personal meaning as part of managing their life experiences.